BENEFITS OF THE PHYSICAL ACTIVITY IN THE HEALTH (Fiep Bulletin - online, 2015)
from the antiquity the physical actitivty has been prescribed in the treatment of several illnesses and as form of preventing pathologies in the human body. In the world modern academic studies  demonstrating the importance of the physical activity in the conditions of the man's health. We know that the lifestyle is one of the factors that causes diseases in the present society, owed mainly to the sedentary life and  unhealty habits of feeding. The physical activity becomes indispensable to avoid several illnesses that cause disability and precocious death. As the people increase their levels of physical conditioning, they move forward towards a better quality of life with full accomplishment social, psychic, spiritual, labor, getting to surpass the stress and the depression. In several ways, the life activates and physical fitness represents economy, reducing futures medical expenses, reducing the need of lingering cares and eliminating deep responsibilities for the family and the society. The physical activity to regulate it serves as a strategy of positive health, as amusement amid the lifestyle disturbed that the people take in the technological world of the present time, where the home, the family and the humanistic values are in an inferiority plan.
Keywords: physical activity; lifestyle; health.